2006
DOI: 10.1097/01.cej.0000195712.64448.ba
|View full text |Cite
|
Sign up to set email alerts
|

Increased suicide risk among Danish women with non-melanoma skin cancer, 1971–1999

Abstract: More suicides than expected (standardized mortality ratio=1.3; 95% confidence interval=1.1-1.6) compared to the population risk were found among Danish women with a diagnosis of non-melanoma skin cancer in the period 1971-1999 but not among men. The increased risk might be associated with a different personality type in this cancer group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…Seventeen studies 1, 16–18, 20, 21, 23, 24, 27, 28, 30, 31, 33, 40, 41, 44, 46 reported the incidence of suicide in cancer patients using a standardised mortality ratio (SMR: ratio of observed deaths to expected deaths) and results ranged from 1 to 11. The wide range of results may be attributable to variations in methodology, cultural differences between countries, sampling frames, populations or sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies 1, 16–18, 20, 21, 23, 24, 27, 28, 30, 31, 33, 40, 41, 44, 46 reported the incidence of suicide in cancer patients using a standardised mortality ratio (SMR: ratio of observed deaths to expected deaths) and results ranged from 1 to 11. The wide range of results may be attributable to variations in methodology, cultural differences between countries, sampling frames, populations or sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The latter explanation is supported by a Danish study, which showed that location of NMSC on the face was more frequent in the suicide group. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Suicide deaths are a significant health burden, which is magnified when also considering suicidal ideation and suicide attempts . Furthermore, approximately 70% of suicides occurring in patients aged >60 years are associated with medical illness, with higher rates among patients who have cancer . Malignancies that are associated with a particularly high risk of suicidal death include head and neck cancers, bladder cancer, lung cancer, foregut cancers, and gynecologic malignancies …”
Section: Introductionmentioning
confidence: 99%